Development Aid and Human Capital Development in Nigeria: A Sector Level-Analysis - Olanrele, Iyabo Adeola; Awode, Segun Subair (Asian Journal of Economics and Empirical Research, 2020)
Developing countries are generally faced with financial gap and budget constraints, and as such are dependent on aids to meet basic social and economic responsibilities. However, there are increasing concerns regarding the effectiveness of aid in developing countries, owing to worsening social and economic outcomes despite the huge amount of aid received from donor countries and institutions. This study therefore examines the effects of sector specific aid such as: health aid and education aid on life expectancy and primary school enrolment rate respectively in Nigeria, controlling for the influence of government expenditures on health and education. The Autoregressive Distributed Lag (ARDL) model was adopted with annual data from 1981 to 2017. Findings revealed that health aid is beneficial as it significantly increases life expectancy by about 0.03%. Recurrent expenditure complemented health aid by increasing life expectancy by 0.03%. However, education aid is detrimental to primary school enrolment as it reduces the rate by 0.07%. Thus, it is concluded that education aid have not had the desired impact on education in Nigeria.